Decontamination of stainless-steel bowls with 80% (w/v) alcohol for 30 s and 60 s: randomized experimental study - Melissa Santiloni Montanha Ramos; Patricia Leme Paniguel; Terue Sadatsune; Kazuko Uchikawa Graziano; Alessandro Lia Mondelli; Silvia Cristina Mangini Bocchi
Objective: to compare the efficacy of 80% (w/v) alcohol, rubbed for 30 and 60 seconds, in the manual processing of stainless-steel wash bowls, after cleaning with running water and neutral detergent. Method: experimental study conducted in a hospital in the state of São Paulo, Brazil, on 50 bowls randomly divided into two groups of 25 bowls each for interventions of 30 and 60 seconds of rubbing with 80% (w/v) alcohol. Results: based on the microbiological analyses collected, before and after the interventions for both groups, partial efficacy of the disinfectant was observed even when extending rubbing time. In both groups, there was a higher prevalence of survival of Pseudomonas aeruginosa, with 14 strains that were resistant to carbapenems, being, specifically, 11 to imipenem and three to meropenem. Conclusion: stainless-steel bed wash bowls decontaminated for reuse by 80% (w/v) alcohol, after cleaning with running water and neutral detergent, showed to be reservoirs of hospital pathogens. The use of bed wash bowls for patients with intact skin would not have worrying consequences, but considering those with non-intact skin and the contamination of professionals' hands, the results in this study justify the search for other decontamination methods or the adoption of disposable bed baths.